Kebiasaan Makan dan Keparahan Acne Vulgaris pada Mahasiswa - Maramis, James Richard; Pitoy, Frendy Fernando; Thomas, Vanesa Giselle (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Acne vulgaris is a dermatological condition that affects both teenagers and adults. While various factors contribute to the severity of acne vulgaris, recent studies are progressively studying the interesting relationship between acne vulgaris and eating habits. Scientific studies have found that certain eating habits such as foods with high fat and glycemic index, products containing milk and energy-dense, and high-calorie foods play a role in exacerbating acne vulgaris. This study aims to determine whether there is a significant relationship between eating habits and the severity of acne vulgaris in grade III and IV students of the Faculty of Nursing, Universitas Klabat.This research is a quantitative research with a descriptive correlation method through a cross-sectional approach. The research sample was taken using a total sampling technique with a total of 205 respondents. Data was collected using the Adolescent Food Habits Checklist (AFHC) questionnaire to measure eating habits, and the Global Acne Grading System (GAGS) to measure the severity of Acne Vulgaris. It was found that most of the students were in the category of poor eating habits, with a total of 114 (55.6%) respondents, and had mild acne vulgaris, with a total 109 (53.2%) respondents. After conducting bivariate analysis using the Spearman's Rho, it was found that the value of p = 0.001; and r=-0.646. There is a significant relationship between eating habits and the severity of acne vulgaris in grade III and IV students of the Faculty of Nursing, Universitas Klabat. The level of coefficient correlation was classified as strong with the negative direction, where the poorer respondent's eating habits are, the higher the severity of acne vulgaris. It is recommended for the students to pay attention to their eating habits by reducing foods high in fat, calories and glycemic index, and starting to eat fruits and vegetables regularly. For further researchers, it is possible to measure the comparison of certain types of food as well as the schedule, and number of food portions consumed and their effect on the severity of acne vulgaris. Keywords: Acne Vulgaris, Eating Habits, Students.  ABSTRAK Acne vulgaris merupakan kondisi dermatologis yang mempengaruhi remaja dan orang dewasa. Sementara berbagai faktor berkontribusi terhadap keparahan acne vulgaris, penelitian-penelitian terbaru secara progresif mempelajari keterkaitan yang menarik antara acne vulgaris dan kebiasaan makan. Studi ilmiah mendapati bahwa kebiasaan makan tertentu seperti makanan dengan lemak dan indeks glikemik tinggi, produk yang mengandung susu dan makanan padat energi serta tinggi kalori berperan dalam memperparah acne vulgaris. Penelitian ini bertujuan untuk mengetahui apakah terdapat hubungan yang signifikan antara kebiasaan makan dengan keparahan acne vulgaris pada mahasiswa tingkat III dan IV Fakultas Keperawatan Universitas Klabat. Penelitian ini merupakan penelitian kuantitatif dengan metode deskriptif korelasi melalui pendekatan cross-sectional. Sampel penelitian diambil dengan menggunakan teknik total sampling dengan jumlah responden sebanyak 205 orang. Data dikumpulkan dengan menggunakan kuesioner Adolescent Food Habits Checklist (AFHC) untuk mengukur kebiasaan makan, dan Global Acne Grading System (GAGS) untuk mengukur derajat keparahan Acne Vulgaris. Ditemukan bahwa sebagian besar mahasiswa berada pada kategori kebiasaan makan yang kurang baik yaitu sebanyak 114 (55,6%) responden, dan memiliki tingkat keparahan acne vulgaris ringan yaitu sebanyak 109 (53,2%) responden. Setelah dilakukan analisis bivariat menggunakan rumus Spearman’s Rho didapati bahwa nilai p=0,00; r=-0,646. Terdapat hubungan yang signifikan antara kebiasaan makan dengan keparahan acne vulgaris pada mahasiswa mahasiswa tingkat III dan IV Fakultas Keperawatan Universitas Klabat.  Tingkat keeratan hubungan tergolong kuat dengan arah hubungan variabel yang bersifat negatif, dimana semakin kurang baik kebiasaan makan responden maka tingkat keparahan acne vulgaris semakin tinggi. Direkomendasikan kepada mahasiswa agar dapat memperhatikan kebiasaan makan mereka dengan mengurangi makanan tinggi lemak, kalori dan indeks glikemik, dan mulai rutin mengonsumsi buah dan sayur. Bagi peneliti selanjutnya dapat mengukur perbandingan dari jenis-jenis makanan tertentu serta jadwal dan jumlah porsi makanan yang dikonsumsi dan pengaruhnya terhadap tingkat keparahan acne vulgaris.  Kata Kunci: Acne Vulgaris, Kebiasaan Makan, Mahasiswa.